Eastern Mediterranean sea levels through the last interglacial from a coastal-marine sequence in northern Israel. (1st August 2016) - Sivan, D.; Sisma-Ventura, G.; Greenbaum, N.; Bialik, O.M.; Williams, F.H.; Tamisiea, M.E.; Rohling, E.J.; Frumkin, A.; Avnaim-Katav, S.; Shtienberg, G.; Stein, M.
Abstract: A last interglacial (Marine Isotope Stage, MIS5e) marine-coastal sequence has been identified along the Galilee coast of Israel, with the type section located at Rosh Hanikra (RH). The microtidal regime and tectonic stability, along with the detailed stratigraphy of the RH shore, make the study region ideally suited for determining relative sea level (RSL) through the MIS5e interval in the eastern Mediterranean. The sequence contains fossilized microtidal subunits at a few meters above the current sea level. Unfortunately, all fossils were found to be altered, so that U-Th datings cannot be considered to represent initial deposition. We contend that U-Th dating of Strombus bubonius shells (recrystallized to calcite) suffices to indicate a lower limit of ∼110 ± 8 ka for the time sea level dropped below the RH sedimentary sequence. The RH-section comprises three main subunits of a previously determined member (the Yasaf Member) : (a) a gravelly unit containing the diagnostic gastropod Strombus bubonius Lamarck ( Persististrombus latus ), which was deposited in the intertidal to super-tidal stormy zone; (b) Vermetidae reef domes indicating a shallow-water depositional environment; and (c) coarse to medium-sized, bioclastic sandstone, probably deposited in the shallow sub-tidal zone. The sequence overlies three abrasion platforms that are cut by tidal channels at elevations of +0.8 m,  +2.6 m and +3.4 m, and which are filled with MIS5e sediments. We present a detailed study of the sequence, with emphasis on stratigraphic, sedimentological, and palaeontological characteristics that indicate sea-level changes. Although without precise absolute dating, the stratigraphic sequence of RH through MIS5e allows us to identify a time-series of RSL positions, using the elevations of three stratigraphic subunits. Reconstructed RSL values range from +1.0 m to +7 m (with uncertainly < 1 m), and most fall within a narrow range of +1.0 to +3.3 m. Toward the end of MIS5e, RSL exceeded about +7 m. Glacial isostatic adjustment (GIA) modelling using multiple ice histories suggests that GIA corrections range between about −1.8 m and +5.4 m. This implies that global mean sea level resided between −0.8 m and +8.7 m during most of MIS5e. The absolute GIA correction would not be constant through the interglacial, and reduces to a range of −1.2 m to+ 2.4 m towards the end of the interglacial. Highlights: A detailed MIS5e coastal stratigraphic sequence from north Israel is presented. Subunits include fossil Strombus bubonius and a Vermetidae reef. MIS5e relative sea level was between +1.0 m and +3.5 m, with a final jump to +7 m. Site specific glacial isostatic adjustment (GIA) modelling is performed. GIA constrains global mean sea level at the end of MIS5e to within +5.8 m and +9.4 m.